2007
DOI: 10.1175/mwr3361.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control of Cloud-to-Ground Lightning Polarity in Severe Storms

Abstract: In this study, it is hypothesized that the mesoscale environment can indirectly control the cloud-to-ground (CG) lightning polarity of severe storms by directly affecting their structural, dynamical, and microphysical properties, which in turn directly control cloud electrification and CG flash polarity. A more specific hypothesis, which has been supported by past observational and laboratory charging studies, suggests that broad, strong updrafts and associated large liquid water contents in severe storms lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
167
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(186 citation statements)
references
References 103 publications
16
167
2
1
Order By: Relevance
“…Contrarily, Rutledge and MacGorman (1988) first suggested that the origin of charge for positive ground flashes in the trailing-stratiform region of MCSs was the rearward advection of positive charge on large aggregates of ice particles from the MCS convective charge centre (leading line) by the mesoscale storm-relative winds (now known as "charge advection mechanism"). More recently, these mechanisms have also been discussed by Gilmore and Wicker (2002), Carey et al (2005), Carey and Buffalo (2007) and Steiger et al (2007a, b). However, the VHF lightning observations by Carey et al (2005) clearly indicate that the "tilted dipole mechanism" and the "charge advection mechanism" are two different mechanism on different scales (convective and mesoscale) that should be considered separately.…”
Section: Discussionmentioning
confidence: 83%
“…Contrarily, Rutledge and MacGorman (1988) first suggested that the origin of charge for positive ground flashes in the trailing-stratiform region of MCSs was the rearward advection of positive charge on large aggregates of ice particles from the MCS convective charge centre (leading line) by the mesoscale storm-relative winds (now known as "charge advection mechanism"). More recently, these mechanisms have also been discussed by Gilmore and Wicker (2002), Carey et al (2005), Carey and Buffalo (2007) and Steiger et al (2007a, b). However, the VHF lightning observations by Carey et al (2005) clearly indicate that the "tilted dipole mechanism" and the "charge advection mechanism" are two different mechanism on different scales (convective and mesoscale) that should be considered separately.…”
Section: Discussionmentioning
confidence: 83%
“…More recently, a primary role for electrical force was brought in as a facilitator of IC tornadogenesis by Patton, Bothun and Sessions [54] with focus on the fact that many tornadic vortices begin at storm mid-level and build downward into ground level tornadoes, more or less in the same manner as originally described by Vonnegut [2,3]. Important connection was established with conditions of high wind shear and large CAPE, in the latter case as already mentioned for the description given in the detailed analysis reported by Carey and Buffalo [20]. In the Patton et al model, a midlevel embryonic tornado structure, enhanced by electrical action, is taken to lead to a central downdraft that acts to build the vortex rotation in a downward direction.…”
Section: Ic Lightning and Tornadogenesismentioning
confidence: 85%
“…The doubly-shaded geographical region covered in Figure 1 may be compared with the not-too-different similarly outlined area covered in Figure 2, as taken from a comprehensive environmental study of a number of severe storm systems reported by Carey and Buffalo [20].…”
Section: Relation To Us Severe Storm Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…7 Lightning data are often used for the nowcasting and tracking of convective thunderstorms 8 because of the close relationship with convective updrafts. 9,10 Aside from its relationship to convection, lightning data can also be used as a validation tool for other nowcasting tools. The objective validation for the RDT product over the European region was done by using the European Cooperation for Lightning Detection data.…”
Section: Volume 111 | Number 7/8mentioning
confidence: 99%